Comparison of manual, digital and lateral CBCT cephalometric analyses - Ricardo de Lima Navarro; Paula Vanessa Pedron Oltramari-Navarro; Thais Maria Freire Fernandes; Giovani Fidelis de Oliveira; Ana Cláudia de Castro Ferreira Conti; Marcio Rodrigues de Almeida; Renato Rodrigues de Almeida (University of São Paulo, 2013)
Objective: The aim of this study was to compare the reliability of three different methods of cephalometric analysis. Material and Methods: Conventional pretreatment lateral cephalograms and cone beam computed tomography (CBCT) scans from 50 subjects from a radiological clinic were selected in order to test the three methods: manual tracings (MT), digitized lateral cephalograms (DLC), and lateral cephalograms from CBCT (LC-CBCT). The lateral cephalograms were manually analyzed through the Dolphin Imaging 11.0™ software. Twenty measurements were performed under the same conditions, and retraced after a 30-day period. Paired t tests and the Dahlberg formula were used to evaluate the intra-examiner errors. The Pearson's correlation coefficient and one-way analysis of variance (ANOVA) tests were used to compare the differences between the methods. Results: Intra-examiner reliability occurred for all methods for most of the measurements. Only six measurements were different between the methods and an agreement was observed in the analyses among the 3 methods. Conclusions: The results demonstrated that all evaluated methodologies are reliable and valid for scientific research, however, the method used in the lateral cephalograms from the CBCT proved the most reliable.